Is it possible to predict sovereign debt default/crises? - A study to identify leading economic indicators while developing an empirical model to predict Sovereign Debt Default - Aneja, Vandit (2011)
There are economic and social costs attached to a country experiencing debt default. As the global economy is integrated, the presence of default in one country can lead to a default in another country with which it has economic and trade associations. This risk of contagion along with adverse economic and social impact of default makes debt default prediction an important topic of research. Correct and early prediction of debt crises allows for the possibility of remedial action and hence the reduction of economic hardship.